Upgrade from SEAP to SECAP: Experience of 6 European Municipalities - Jekabsone Anda (Sciendo, 2021)
Since 2008 many municipalities in the European Union have taken part in the Covenant of Mayors (CoM) initiative and have developed Sustainable Energy Action Plans (SEAP) to contribute to climate change mitigation. To respond to new policy goals for 2030, the CoM has expanded its focus and since 2018 requires municipalities to cover climate adaptation actions. The main aim of this paper is to analyse the first experiences of six municipalities from Spain, Portugal and Latvia in upgrading their existing Sustainable Energy Actions Plans to Sustainable Energy and Climate Action Plans (SECAP). SECAPs were developed through a participatory process involving all relevant local stakeholders, to gain maximum understanding and acceptance. Each municipality implemented climate adaption actions to demonstrate the need for adaptation and the ways it can be accomplished.